An Estimated Dynamic Stochastic General Equilibrium Model of the Jordanian Economy - Poghosyan, Tigran; Beidas-Strom, Samya (Washington, D.C. : International Monetary Fund, 2011)
This paper presents and estimates a small open economy dynamic stochastic general-equilibrium model (DSGE) for the Jordanian economy. The model features nominal and real rigidities, imperfect competition and habit formation in the consumer's utility function. Oil imports are explicitly modeled in the consumption basket and domestic production. Bayesian estimation methods are employed on quarterly Jordanian data. The model's properties are described by impulse response analysis of identified structural shocks pertinent to the economy. These properties assess the effectiveness of the pegged exchange rate regime in minimizing inflation and output trade-offs. The estimates of the structural parameters fall within plausible ranges, and simulation results suggest that while the peg amplifies output, consumption and (price and wage) inflation volatility, it offers a relatively low risk premium.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet